The investigator - Sandford, John, 1944 February 23- (A Letty Davenport novel, 2022)
"Letty Davenport, the brilliant and tenacious adopted daughter of Lucas Davenport, takes the investigative reins in the newest thriller from #1 bestselling author John Sandford"--